Response of irrigated crops to micronutrients application in the submédio São Francisco region - Farias, Clementino Marcos Batista de; Pereira, José Ribamar (Pesquisa Agropecuaria Brasileira, 2000)
An analysis of eight experiments from 1976 to 1996 was carried out involving irrigated industrial tomato, garlic and beans crops in the Submédio São Francisco region, Northeast Brazil, with the objective of examining their response to micronutrients. The treatments of the experiments consisted of presence and absence of boron, copper, iron, manganese, molybdenum and zinc in a randomized complete block design with four replications. There was no response of garlic and beans to micronutrient application. The tomato crop responded to boron application in only one of the experiments with an increase of 12.86 ton/ha of fruits.